2017
DOI: 10.1139/cjfas-2016-0076
|View full text |Cite
|
Sign up to set email alerts
|

Summer temperature regimes in southcentral Alaska streams: watershed drivers of variation and potential implications for Pacific salmon

Abstract: Abstract:Climate is changing fastest in high-latitude regions, focusing our research on understanding rates and drivers of changing temperature regimes in southcentral Alaska streams and implications for salmon populations. We collected continuous water and air temperature data during open-water periods from 2008 to 2012 in 48 nonglacial salmon streams across the Cook Inlet basin spanning a range of watershed characteristics. The most important predictors of maximum temperatures, expressed as mean July tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 79 publications
2
47
0
Order By: Relevance
“…Empirical stream thermal sensitivity has been widely used to characterize historic stream temperature conditions and also to predict how streams might respond to future climate warming (Isaak et al, , ; Mauger et al, ). These types of methods, which rely on regressions between stream and air temperatures, have been criticized for not adequately representing the underlying processes controlling stream temperature (Arismendi et al, ; Johnson, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Empirical stream thermal sensitivity has been widely used to characterize historic stream temperature conditions and also to predict how streams might respond to future climate warming (Isaak et al, , ; Mauger et al, ). These types of methods, which rely on regressions between stream and air temperatures, have been criticized for not adequately representing the underlying processes controlling stream temperature (Arismendi et al, ; Johnson, ).…”
Section: Introductionmentioning
confidence: 99%
“…Luce et al (2014) argued that using interannual mean temperatures, such as mean August or mean summer temperatures, is preferable over subannual temperatures since models fit to subannual temperatures will be confounded by annual hysteresis in the relation between stream temperature and solar radiation. However, a drawback of using interannual temperatures is that few long-term records exist, and although with increased and continuing monitoring efforts, this situation is changing (Isaak et al, 2017;Luce et al, 2014).Empirical stream thermal sensitivity has been widely used to characterize historic stream temperature conditions and also to predict how streams might respond to future climate warming (Isaak et al, 2016(Isaak et al, , 2018Mauger et al, 2017). These types of methods, which rely on regressions between stream and air temper-…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Fellman et al (2014) observed slopes of between −0.180 and 1.282 across nine watersheds in Alaska depending on glacial influence, while Mauger et al (2017) observed slopes of between 0.32 and 1.51 across 48 non-glacial streams in Alaska which related to mean elevation and catchment area. Similarly, Tague et al (2007) observed systematic regional differences in T w -T a relationships in western Oregon that depended on local hydrogeology and concluded that under such circumstances air temperature alone (i.e.…”
Section: T W -T a Relationshipsmentioning
confidence: 97%
“…Many studies have shown that within-year temporal relationships between T w and T a (often termed thermal or climate sensitivity) can be highly variable between sites and catchments, and importantly this variability relates to regional, hydrological and landscape controls (Tague et al, 2007;Kelleher et al, 2012;Krider et al, 2013;Chang and Psaris, 2013;Hilderbrand et al, 2014;Segura et al, 2015;Mauger et al, 2017). For example, Fellman et al (2014) observed slopes of between −0.180 and 1.282 across nine watersheds in Alaska depending on glacial influence, while Mauger et al (2017) observed slopes of between 0.32 and 1.51 across 48 non-glacial streams in Alaska which related to mean elevation and catchment area.…”
Section: T W -T a Relationshipsmentioning
confidence: 99%